Foreign capital and economic development : Japan, India, and Canada; studies in some aspects of absorption of foreign capital. - Islam, Nurul (Rutland, Vt., C. E. Tuttle Co., 1960)
This work is Professor Islam's doctoral dissertation, written in 1953-55 at Harvard University. His object is to throw light on the determinants of " capacity to absorb capital," by way of a study of the contrasting historical experiences of Japan, India (undivided) and Canada, mostly during the period from the turn of the present century to the early 1940s. It is, however, clear from early on that Professor Islam's principal concern is to discover in the record of international capital movements and of the associated developments those factors which have given rise to all-round cumulative domestic economic growth and successful debt service in borrowing countries.
Includes bibliographical references and index.
rpm 10/11/2017
Loans
Keywords: Investments, Foreign; Economic development; Economic history; Japan; Canada; India